STUDIES ON PHOSPHOLIPASE C FROM MELIA AZADIRACHTA SEEDS (Journal of Sciences, Islamic Republic of Iran)
3,5- dinitrobenzoyl chloride-pyridine system has been used for dehydration of aldoximes and carboxamides at room temperature